Spillover effects of credit default risk in the euro area and the effects on the euro: A GVAR approach - Timo Bettendorf (Deutsche Bundesbank, 2016)
During the 2008 financial crisis, increasing risk and spillovers became a main concern for policy makers and banks. In addition, changes in sovereign and bank risk are believed to have had strong effects on world-wide exchange rates. This paper aims to analyze these dynamics empirically. We estimate a Global VAR (GVAR) model for nine EMU countries plus Japan, the United Kingdom as well as the United States and identify structural risk shocks using sign restrictions, which are based on a theoretical model by Acharya et al. (2014, JF). Our results indicate that spillover effects of general risk are much stronger than those of bailouts. Furthermore, we demonstrate that the Euro depreciates significantly against the Yen and US Dollar following general risk shocks in the euro area and only to a small extent following bailout shocks. The Pound Sterling is not affected by any of these shocks. The Euro variability is, from the EMU perspective, mainly driven by shocks stemming from large countries (e.g. Germany, France and Italy). However, shocks from third countries also play an important role.
Keywords: C55; F31; H63; 330; credit default swaps; bailouts; exchange rates; global var